Biometric evaluation of the use in different sources of nitrogen in safrinha corn - Oliveira, Danielly Terra Monteiro; Andrade, Christiano Lima Lobo de; Cabral Filho, Fernando Rodrigues; Teixeira, Marconi Batista; Ferreira, Tarimar Martins (Brazilian Journal of Science, 2023)
Corn is defined as “the sustenance of life”, being the main raw material in the daily diet of a large part of the world’s population. It is a very efficient plant in converting solar radiation into biomass, as a result of its C4-type photosynthetic mechanism associated with its high leaf area, the biometric evaluation of is a simple test that provides a summary assessment of the risk or general form of a possible disease., which can be diagnosed. The objective of this work was to evaluate the biometric development and productivity of maize in different nitrogen sources. The test was conducted in the experimental area by the company Pulveriza Soluções Agrícolas, in the city of Rio Verde, Goiás, Brazil, located in the southwest region of the state. The corn was sown on 01/29/2022, using a 5-line seeder with a horizontal disc seed distribution system. The biometric characteristics of the corn crop were measured, measuring two plants per plot: plant height; ear insertion height; stem diameter; number of sheets; leaf area; leaf area index and dry weight of the leaves, the leaves were dried in an oven with forced air circulation for 72 hours at 65 °C. With this work, we were able to point out that the use provides an increase in intercepted photosynthetically active radiation, light interception efficiency and total chlorophyll in corn leaves, cultivated in the second crop, the use of nitrogen, regardless of source and dose, promotes an increase in dry weight.